SOSIO EKONOMI DAN POLA PEMANFAATAN KAWASAN PENYANGGA CAGAR ALAM BUKIT BUNGKUK OLEH MASYARAKAT DI SEKITAR KAWASAN - Salman Yasir; Eko Sutrisno (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2023)
Bukit Bungkuk wildlife sanctuary is located in Kampar Regency, Riau Province with an area of 12,828.88 Ha. Based on the Decree of the Minister of Forestry No. 3917/Menhut-VII/KUH/2014, this area is designated as a conservation area with wildlife sanctuary status. The socio-economic conditions and land use patterns in this area was carried out through structured interviews with the determination of respondents by purposive sampling. Communities in bordered of Bukit Bungkuk wildlife sanctuary covers by District XIII Koto Kampar, Kuok and Salo. Generally, people who live in border areas are natives of Kampar Regency. The pattern of utilization of the Bukit Bungkuk wildlife sanctuary by the community includes harvesting non-timber forest products and land use for plantations. The goverment institution as the manager of Bukit Bungkuk wildlife sanctuary comes with the new paradigms which are the communities of area bordered treatment by empowerment schemes. This effort to quarantee the stabilization of conservation areas inline with the livelihood of the communities bordered..